Nomenclatural changes for some Orthoptera (Ensifera and Caelifera) - Özdi̇kmen, Hüseyi̇n (Zootaxa, 2008)
Three proposed genus group names in the family Tettigoniidae, Euschmitiidae and Eumastacidae are nomenclaturally invalid, as the genus group names have already been used by different authors in other animal groups (Coleoptera and Hemiptera). In accordance with Article 60 of the International Code of Zoological Nomenclature, I propose substitute names for these names.